2009
DOI: 10.1152/ajpendo.90876.2008
|View full text |Cite
|
Sign up to set email alerts
|

Iodide deficiency-induced angiogenic stimulus in the thyroid occurs via HIF- and ROS-dependent VEGF-A secretion from thyrocytes

Abstract: Vascular supply is an obvious requirement for all organs. In addition to oxygen and nutrients, blood flow also transports essential trace elements. Iodine, which is a key element in thyroid hormone synthesis, is one of them. An inverse relationship exists between the expansion of the thyroid microvasculature and the local availability of iodine. This microvascular trace element-dependent regulation is unique and contributes to keep steady the iodide delivery to the thyroid. Signals involved in this regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
(43 reference statements)
3
31
0
Order By: Relevance
“…On the other hand, five subjects (14.7%) among them were diagnosed as having HID. The incidence of HID is surprisingly low in view of the extremely low iodine intake but may actually be in line with other data from population studies [9][10][11][12][13][14] or may reflect difficulty in recognizing hypothyroid state in these patients or may be due to thyroid adaptive processes [15][16][17][18]. Possibly SMID patients, the targets of this study, might be at risk of developing disorders with a poor response of TSH that renders their hypothyroidism difficult to diagnose.…”
Section: Stagesupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, five subjects (14.7%) among them were diagnosed as having HID. The incidence of HID is surprisingly low in view of the extremely low iodine intake but may actually be in line with other data from population studies [9][10][11][12][13][14] or may reflect difficulty in recognizing hypothyroid state in these patients or may be due to thyroid adaptive processes [15][16][17][18]. Possibly SMID patients, the targets of this study, might be at risk of developing disorders with a poor response of TSH that renders their hypothyroidism difficult to diagnose.…”
Section: Stagesupporting
confidence: 84%
“…Some experimental reports document that early thyroid adaptation develops after short-term (about one month) iodine deficiency, e.g. angiogenesis in the thyroid gland to increase iodine absorption without TSH stimulation, or tissue-selective acceleration of deiodinase activity resulting in T4 to T3 conversion [15][16][17][18]. Therefore, modest increase TSH, high normal or increased T3, and low normal or decreased T4 might be detected in iodine deficient state [19].…”
Section: Stagementioning
confidence: 99%
“…Oxidative stress resulting from overproduction of ROS is an important intermediary step in the pathogenesis of preeclampsia and in human trophoblast differentiation [29]. Previous studies have shown that iodine deprivation induce VEGF expression through HIF-1α activation mediated by increasing ROS in thyroid cells [10]. In this study, iodine deprivation increases ROS and Snail mRNA expressions, although HIF-1α mRNA expression does not change.…”
Section: Discussionmentioning
confidence: 47%
“…Peroxisome proliferator-activated receptor gamma (PPARgamma) induces trophoblast differentiation through GCM-1 that promotes differentiation of underlying cytotrophoblast cells into the outer syncytiotrophoblasts layer [6,7]. In the thyroid gland, intracellular iodine concentration plays an important role in redox balance by modulating hydrogen peroxide generation [8,9] and thyroid iodine deficiency induced intracellular production of reactive oxygen species (ROS) that stabilizes HIF-1α protein and then the expression and secretion of vascular epithelial growth factor (VEGF) for novel blood vessels [10]. It has been proposed that in thyroid and extrathyroid tissues, iodolipids are the mediators of iodine properties, through PPAR-gamma activation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid VEGF is upregulated by estrogen, and thyroid weight, vascular area, and VEGF protein expression are lower in ovariectomized rats in comparison with sham-operated rats and ovariectomized rats treated with 17b-estradiol (de Araujo et al 2010). Interestingly, in PCCL3 cells, an increase in intracellular ROS, elicited by iodide deprivation, induces HIF-1a and VEGF protein expression, but concomitant treatment with the antioxidant N-acetyl-cysteine abolishes the effects of iodide deprivation (Gérard et al 2009). Thus, it is tempting to speculate that NOX4 could also be involved in the regulation of thyroid VEGF expression induced by estradiol and iodide deprivation.…”
Section: Estrogen Effects On Thyroid Redox Balancementioning
confidence: 99%